Sistem Informasi Data Alumni Berbasis Web Di SMP Negeri 20 Kota Surakarta (SinTani) - Evafurati Tina Ajiyastuti; Veronica Noviametti Ariyani; Tutik Rahayu; Mursid Dwi Hastomo; Tri Budi Santosa (Indonesian Journal of Information Technology and Computing (IMAGING), 2025)
SMP Negeri 20 Surakarta does not yet have a structured information system for digitally managing alumni data. Alumni data collection has been carried out manually, which may result in incomplete, inaccessible, and uncentralized data. This study aims to design and develop a web-based alumni information system to facilitate the process of recording, updating, and utilizing alumni data effectively. The development method used is the waterfall model, which consists of requirements analysis, system design, implementation, testing, and maintenance stages. The system is built using PHP programming language and MySQL database, and designed with a simple and responsive interface to be easily accessible by both administrators and alumni. The implementation results show that the system can be used to input alumni data, update information, and display data based on certain criteria, such as graduation year. Alumni can also access the system to update their own data independently. With this system, alumni data management becomes more organized and efficient, and can support various school needs such as reporting, accreditation, and long-term relationships with graduates. The system is also expected to be further developed to become more optimal and better suited to users' needs in the future.